The Role of Innovation Activity in The Conditions of Economy Globalization - Sattorkulov Obidkul Turdikulovich; Buriboev Erkinjan Narbay ugli (European Science Publishing, 2023)
This article presents the main ways in which innovation can have a positive impact on economic growth, welfare of the population, economic structure, social image of society and various sectors of the economy, innovation opportunities, their application and development prospects.
Keywords: innovation, novation, science, new development, innovation, innovation infrastructure, innovation activity, innovation process.